Adsorpsi Karbon Aktif dari Sabut Kelapa (Cocos Nucifera) Terhadap Penurunan Fenol - Astriah Abdullah; Asri Saleh; Iin Novianty (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2013)
Coconut coir can be used as an activated carbon for phenol removal, because of carbon element which is containing in Coconut coir make it to own a potency as an activated carbon. Research on activated carbon adsorption of phenol to the decline of coconut coir (Cocos nucivera) has been performed. This study begins with the dehydration and carbonization stage. Coconut coir activated carbon with 3 activator namely sulfuric acid (H2SO4), sodium hydroxide (NaOH) and zinc chloride (ZnCl2). Coconut coir activated carbon in this study using a variable dose of 500 mg carbon, 1000 mg and 1500 mg. This study aimed to determine the characteristics of the water content, the adsorption capacity of phenol on activated carbon from coconut husk carbon activation results and determine the maximum adsorption capacity of activated carbon from coconut husk carbon in the adsorption of phenol. Activators most good at absorbing phenol is sodium hydroxide (NaOH) with the absorption efficiency of 93.01% at a mass of 1.5 g.